2019
DOI: 10.1080/14658011.2019.1626596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different size complex fillers on thermal conductivity of PA6 thermal composites

Abstract: Nylon 6 (PA6) thermal conductive composites were prepared by melt blending with different sizes of spherical Al 2 O 3 and AlN and the filling amount was 60 wt%. This paper explored the effects of different particle sizes and filler kinds on the thermal conductivity and mechanical properties of the composites. The results showed that the composites filled with AlN and spherical Al 2 O 3 had higher thermal conductivity than the composites filled with single filler under the same filling amount. When the mass rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Besides, the incorporation of different-sized Al 2 O 3 endows composites with better thermal diffusion coefficient, which may be concluded to better distribution of Al 2 O 3 within the composite. 32
Figure 8.Thermal conductivity and thermal diffusion coefficient of sample n (a) n = 1, 2, 3…8 (b) n = 9, 10, 11…16 (c) PE, S20, S30, S50 and S70.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the incorporation of different-sized Al 2 O 3 endows composites with better thermal diffusion coefficient, which may be concluded to better distribution of Al 2 O 3 within the composite. 32
Figure 8.Thermal conductivity and thermal diffusion coefficient of sample n (a) n = 1, 2, 3…8 (b) n = 9, 10, 11…16 (c) PE, S20, S30, S50 and S70.
…”
Section: Resultsmentioning
confidence: 99%
“…16,26,30,31 In addition to the type of fillers, filler size, shape and content also affect the performance of the composite material. [32][33][34][35][36] Zhao et al 37 prepared an epoxy-based material using the BN sheets and microspheres, where the BN microspheres play a role of bridge to connect the adjacent flakes. The composites with a filler loading of 30 wt % exhibited a thermal conductivity of 1.148 WÁm À1 ÁK À1 .…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid filler network shortens the distance between fillers, avoids heat passing through the matrix with low thermal conductivity, and promotes heat conduction. Li et al [ 132 ] introduced hybrid spherical alumina with a diameter of 18 μm and 48 μm into nylon 6, and the influence of the ratio of different particle sizes on the thermal conductivity of the composite was systematically studied. It was found that the thermal conductivity of the prepared composite with hybrid fillers at various mass ratios was always higher than that achieved by a single particle size filler.…”
Section: Strategies For Enhancing Thermal Conductivity Of Polymer Com...mentioning
confidence: 99%
“…Burda et al 28 used nano silica particles, micron rubber and micron calcium carbonate as fillers to fill the oxygen re‐oxidizing resin matrix, and the fracture toughness increased by 60%. Li et al 29 prepared nylon 6 (PA6) thermal conductive composite by melting blending containing AlN and spherical Al 2 O 3 of different sizes. Under the same filler content, the thermal conductivity and thermal diffusivity of the composites filled with AlN and spherical Al 2 O 3 was 2.44 W/m K and 0.72 mm 2 /s, respectively, which were higher than those of the composites filled with single filler.…”
Section: Introductionmentioning
confidence: 99%